The role of secondary assists in basketball - an analysis of its characteristics and effect on scoring - Supola, B.; Hoch, T.; Baca, A. (International Journal of Performance Analysis in Sport, 2022)
Basketball leagues track basic statistics for many decades and the number of metrics expand quickly. However, the "pass that leads to an assist", which is frequently - according to the most successful coach Phil Jackson - the most important pass of the possession, remained mainly overlooked by experts and analysts alike. With the help of NBA`s SportVU positional data we analyse the characteristics and effects of this event through more than 500 games. Results show that teams having more secondary assists create space in areas related to higher expected points, get more open and therefore obtain better quality shots. The number of secondary assists might turn out to be one of the best metrics to measure quality ball movement.